CT-P17 Adalimumab Biosimilar in Patients with Moderate-to-Severe Chronic Plaque Psoriasis: An Open-Label Extension of a Phase 3 Interchangeability Study - Pariser, David M.; Lebwohl, Mark G.; Jaworski, Janusz; Trefler, Jakub; Daniluk, Stefan; Dudek, Anna; Baran, Wojciech; Owczarek, Witold; Brzewski, Pawel; Sikora, Mariusz; Krogulec, Marek; Kim, SungHyun; et al. (Dermatology and therapy, 2025)
Introduction A 27-week analysis of this phase 3 study demonstrated the interchangeability of the adalimumab biosimilar CT-P17 and reference adalimumab. The current 52-week analysis reports secondary data from the open-label extension period (OLE) of the study. Methods In this randomized, double-blind, active-controlled phase 3 study, adults with moderate-to-severe chronic plaque psoriasis received (via prefilled syringe) 80 mg subcutaneous reference adalimumab on day 1, then 40 mg 1 week later, and every other week (EOW) until week 11. At week 13, patients were randomized (1:1) to continue reference adalimumab (“continuous” group) or undergo repeated switching between CT-P17 and reference adalimumab (“switching” group) until week 25. Thereafter, patients entered an OLE and received 40 mg CT-P17 EOW from week 27 to 49, with an end-of-study visit at week 52. Here we present findings from the OLE. Pharmacokinetics (PK), efficacy (including mean percent improvement from baseline in Psoriasis Area Severity Index [PASI] score), safety, and immunogenicity were evaluated. Post hoc subgroup analyses were also conducted. Results Of 327 patients who initiated the OLE, 152 and 160 patients from the switching group and continuous group, respectively, completed the study. Mean serum concentrations were similar between groups throughout the OLE. Efficacy improvements observed up to week 27 were maintained during the OLE and were comparable between groups. At week 52, overall mean (standard deviation [SD]) improvement from baseline in PASI score was 90.34% (16.59). Safety profiles were similar between groups, and immunogenicity did not increase during the OLE. The mean (SD) percent improvement from baseline in PASI score was slightly lower in patients who were antidrug antibody (ADA)-positive versus those who were ADA-negative (89.57 [17.27] versus 97.29 [4.08]) at week 52. Conclusions PK, efficacy, safety, and immunogenicity findings remained consistent throughout the OLE, regardless of prior treatment, and were generally comparable across timepoints. Trial registration ClinicalTrials.gov: NCT05495568. Plain Language Summary A biosimilar is a medicine made using living cells that is highly similar to an original (“reference”) medicine. As biosimilars are typically cheaper than reference medicines, their use may make it easier for patients to get treatment. CT-P17, approved to treat inflammatory conditions, is a biosimilar of a reference medicine called adalimumab. CT-P17 is highly concentrated (40 mg/0.4 mL) and does not contain citrate, which may reduce pain at the injection site. This study is important because it aimed to demonstrate that patients with psoriasis could switch between CT-P17 and reference adalimumab safely and without losing effectiveness and secure status known as “interchangeability”. This would allow pharmacists to dispense CT-P17 directly when reference adalimumab is initially prescribed, providing flexibility, timely treatment access, and potentially reducing patient costs. In this study, patients with psoriasis were switched between CT-P17 and adalimumab multiple times (switching period). Results showed that CT-P17 can be used interchangeably with reference adalimumab by demonstrating similar pharmacokinetics (how the body absorbs, processes, and excretes a drug), effectiveness, safety, and immunogenicity (risk of unwanted immune reactions) between patients who switched medicines and those receiving reference adalimumab throughout. These results have been previously published. This article reports results from the last part of the study, which followed the switching period. In this part, all patients received CT-P17 every other week. Pharmacokinetics, effectiveness, safety, and immunogenicity findings remained similar to those observed during the switching period. These results provide further support for the interchangeability of CT-P17 and reference adalimumab.